Human resource management. - University of Minnesota. Libraries. Publishing; BC Open Textbook Project; BCcampus (University of Minnesota Libraries Publishing, 2016)
"Human Resource Management teaches HRM strategies and theories that any manager-not just those in HR-needs to know about recruiting, selecting, training, and compensating people"--BCcampus website.
The Role of Human Resources -- Developing and Implementing Strategic HRM Plans -- Diversity and Multiculturalism -- Recruitment -- Selection -- Compensation and Benefits -- Retention and Motivation -- Training and Development -- Successful Employee Communication -- Managing Employee Performance -- Employee Assessment -- Working with Labor Unions -- Safety and Health at Work -- International HRM.
Author removed at request of original publisher. This edition adapted from a work originally produced in 2011 by a publisher who has requested that it not receive attribution.
Human Resource Management by [Author removed at request of original publisher] is licensed under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License, except where otherwise noted.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Mode of access: World Wide Web.
Online version, 2016 edition; title from online version (viewed on May 19, 2017).
Keywords: Personnel management -- Textbooks; Electronic books